Modeling local non-homogeneity in electroconductive non-ferromagnetic thermoelastic solid - Nahirnyj, T. S.; Senyk, Y. A.; Tchervinka, K. A. (Publishing House of Lviv Polytechnic National University, 2014)
We consider the key systems describing steady state of a locally inhomogeneous electroconductive non-ferromagnetic solid within framework of the local gradient approach in thermomechanics. An arbitrarily chosen subdomain of the solid is regarded as a thermodynamically open system that can exchange by mass with environment. It is assumed that this exchange occurs suddenly at the initial time when the body structure is instantly set. The mass sources are introduced into the model to conform the actual and reference body states. The sources are associated with method of body surface forming. Розглянуто ключовi системи рiвнянь, що описують рiвноважний стан локально неоднорiдного електропровiдного неферомагнiтного термопружного тiла у рамках локально градiєнтного пiдходу у термомеханiцi. Довiльно видiлена пiд область тiла розглядається як термодинамiчно вiдкрита система, що може обмiнюватись масою з оточенням. Припускається, що такий обмiн вiдбувається миттєво у початковий момент часу при встановленнi структури тiла. У розгляд введено джерела маси, що дозволило узгодити актуальний та вiдлiковий стани у моделi. Джерела маси пов’язано iз способом формування поверхнi тiла.
Моделювання локальної неоднорiдностi у електропровiдному неферомагнiтному термопружному тiлi
Keywords: local gradient approach; near-surface non-homogeneity; size effect; electroconductive non-ferromagnetic thermoelastic solid; double electric layer; локально градiєнтний пiдхiд; приповерхнева неоднорiднiсть; розмiрний ефект; електропровiдне неферомагнiтне термопружне тiло; подвiйний електричний шар